2018
DOI: 10.1264/jsme2.me17203
|View full text |Cite
|
Sign up to set email alerts
|

Taxon Richness of “Megaviridae” Exceeds those of Bacteria and Archaea in the Ocean

Abstract: Since the discovery of the giant mimivirus, evolutionarily related viruses have been isolated or identified from various environments. Phylogenetic analyses of this group of viruses, tentatively referred to as the family “Megaviridae”, suggest that it has an ancient origin that may predate the emergence of major eukaryotic lineages. Environmental genomics has since revealed that Megaviridae represents one of the most abundant and diverse groups of viruses in the ocean. In the present study, we compared the tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
71
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 93 publications
8
71
0
1
Order By: Relevance
“…The discovery of giant viruses in the early 21 st century has revived the debate on the nature of viruses and their role in evolution 113 . The 1µm-long particles of pithoviruses 14 can be seen under a light microscope and the 2.5Mb-long genomes of pandoraviruses, larger than those of many cellular organisms, encode for more than 2,000 proteins, mostly ORFans 15 .…”
mentioning
confidence: 99%
“…The discovery of giant viruses in the early 21 st century has revived the debate on the nature of viruses and their role in evolution 113 . The 1µm-long particles of pithoviruses 14 can be seen under a light microscope and the 2.5Mb-long genomes of pandoraviruses, larger than those of many cellular organisms, encode for more than 2,000 proteins, mostly ORFans 15 .…”
mentioning
confidence: 99%
“…However, this is in stark contrast to genomes of large and giant viruses of the NCLDV, which can be up to several megabases (Abergel et al, 2015;Fischer, 2016) . Importantly, recent studies showed that these viruses are among the most diverse and abundant entities in marine systems (Hingamp et al, 2013;Mihara et al, 2018) and are also found in a wide range of non-marine ecosystems (Graham et al, 2019;Kerepesi and Grolmusz, 2017;Roux et al, 2017;Schulz et al, 2018Schulz et al, , 2017bVavourakis et al, 2016) .…”
Section: Introductionmentioning
confidence: 99%
“…The investigation 100 of eukaryotic viruses based on environmental genomics has long been difficult because of 101 their lower concentration in the water column compared with prokaryotic dsDNA viruses 102 (Hingamp et al 2013). Deep sequencing of planktonic community DNA and RNA, as 103 carried out in Tara Oceans, has enabled the identification of marker genes of major viral 104 groups infecting eukaryotes and begun to reveal that these groups represent a sizeable 105 fraction of the marine virosphere (Hingamp et al 2013;Allen et al 2017;Moniruzzaman 106 et al 2017;Carradec et al 2018;Mihara et al 2018). In the present study, we identified 107 several hundred marker-gene sequences of nucleocytoplasmic large DNA viruses 108 (NCLDVs; so-called "giant viruses") in the prokaryotic size fraction.…”
Section: Introductionmentioning
confidence: 99%